Pengaruh Karakteristik Pemerintah Daerah, Opini Audit, dan Rasio Kemandirian Terhadap Pengungkapan Laporan Keuangan Pemerintah Daerah - Izzatunisa’, Rifky Farah; Afifudin, Afifudin; Rudiningtyas, Dyah Arini (Universitas Islam Malang, 2024)
This research aims to determine the influence of local government characteristics, audit opinion, independence ratio on the disclosure of local government financial reports. This quantitative research uses secondary data originating from regional government financial reports from 37 districts and cities in East Java Province for the period 2019 to 2022 obtained from the BPK or Financial Audit Agency website. This research determines the sample using the purposive sampling method. The independent variables used in this research are local government characteristics which are measured using the human development index, audit opinion and independence ratio. The dependent variable in this research is the disclosure of local government financial reports. The results of this research explain that regional government characteristic variables and audit opinions have a positive influence on the disclosure of regional government financial reports. Meanwhile, the independence ratio has a negative effect on the disclosure of regional government financial reports in districts and cities in East Java Province.Keywords: Regional government characteristics, audit opinion, independence ratio, disclosure of regional government financial reports